Factors Related to the Quality of Life of Diabetes Mellitus Patients in the Matani Community Health Center Work Area, Tomohon City - Sendy W. Lumanauw; Junita M. Pertiwi; Erling D. Kaunang; Grace D. Kandou; Wulan PJ Kaunang (CV. Inara, 2025)
This study aims to analyze factors associated with quality of life of diabetes mellitus patients in the Matani Community Health Center Work Area, Tomohon City. This study specifically examines the relationship between duration of disease, depression, anxiety, stress, and family support on quality of life in diabetes mellitus patients. The study used a cross-sectional design with 168 respondents selected through consecutive sampling. Data were collected through interviews using standardized instruments, the DASS 21, HDFSS, and Euro-QoL. The data were analyzed using the chi-square test and multivariate logistic regression. The results showed a significant association between duration of disease and stress with quality of life in diabetes mellitus patients (p < 0.05). Patients with a duration of >5 years of suffering are 3 times more likely to have a poor quality of life and patients with severe stress are 2 times more likely to have a poor quality of life. These findings indicate the importance of increasing awareness in adherence to diabetes mellitus management, especially for patients who have suffered for a long time and improving psychosocial monitoring services for diabetes mellitus patients, especially regarding stress management, and becoming the basis for strengthening primary health care programs in diabetes mellitus management so that the quality of life of diabetes mellitus patients improves.